The GRB–SLSN connection: misaligned magnetars, weak jet emergence, and observational signatures. Issue 2 (9th January 2018) - Margalit, Ben; Metzger, Brian D; Thompson, Todd A; Nicholl, Matt; Sukhbold, Tuguldur
Abstract: Multiple lines of evidence support a connection between hydrogen-poor superluminous supernovae (SLSNe) and long-duration gamma-ray bursts (GRBs). Both classes of events require a powerful central energy source, usually attributed to a millisecond magnetar or an accreting black hole. The GRB–SLSN link raises several theoretical questions: What distinguishes the engines responsible for these different phenomena? Can a single engine power both a GRB and a luminous SN in the same event? We propose a unifying model for magnetar thermalization and jet formation: misalignment between the rotation (Ω ) and magnetic dipole (μ ) axes dissipates a fraction of the spin-down power by reconnection in the striped equatorial wind, providing a guaranteed source of 'thermal' emission to power the supernova. The remaining unthermalized power energizes a relativistic jet. We show that even weak relativistic jets of luminosity ∼10 46  erg s −1 can escape the expanding SN ejecta implying that escaping relativistic jets may accompany many SLSNe. We calculate the observational signature of these jets. We show that they may produce transient ultraviolet (UV) cocoon emission lasting a few hours when the jet breaks out of the ejecta surface. A longer lived optical/UV signal may originate from a mildly relativistic wind driven from the interface between the jet and the ejecta walls, which could explain the secondary early-time maximum observed in some SLSNe light curves, such as LSQ14bdq. Our scenario predicts a population of GRB from on-axis jets with extremely long durations, potentially similar to the population of 'jetted-tidal disruption events', in coincidence with a small subset of SLSNe.